Sphingolipids in neurodegenerative diseases - Pan, Xueyang; Dutta, Debdeep; Lu, Shenzhao; Bellen, Hugo J. (Frontiers in Neuroscience, 2023)
Neurodegenerative Diseases (NDDs) are a group of disorders that cause progressive deficits of neuronal function. Recent evidence argues that sphingolipid metabolism is affected in a surprisingly broad set of NDDs. These include some lysosomal storage diseases, hereditary sensory and autonomous neuropathy, hereditary spastic paraplegia, infantile neuroaxonal dystrophy, Friedreich’s ataxia, as well as some forms of amyotrophic lateral sclerosis and Parkinson’s disease. Many of these diseases have been modeled in Drosophila melanogaster and are associated with elevated levels of ceramides. Similar changes have also been reported in vertebrate cells and mouse models. Here, we summarize studies using fly models and/or patient samples which demonstrate the nature of the defects in sphingolipid metabolism, the organelles that are implicated, the cell types that are initially affected, and potential therapeutics for these diseases.